Work attitudes in transition: Some implications for management of organizational change in Bulgaria - Snejana Ilieva (Journal for East European Management Studies, 1999)
The article deals with the peculiarities of work attitudes in conditions of transition to market economy. Dynamics of work attitudes are traced in a seven-year period - 1990-1997. It is shown how work attitudes could be described right after the fall of the socialist system, that means at beginning of the transition from planned to market economy and what changes in work attitudes occur under the influence of the difficult transition to market economy. A practical consequence of the study is that organizational change will not be effective if carried out in a random and unpredictable way, without consideration of people's values and attitudes. From this viewpoint the implementation of new approaches of human resource management is a requirement for the success of change, as well as for organizational efficiency. – – Der Artikel befaßt sich mit den Besonderheiten von Arbeitseinstellungen unter den Bedingungen der Transformation von Plan zum Markt. Dazu werden über eine Periode von sieben Jahren (1990-1997) die Dynamiken von Arbeitseinstellungen nachgezeichnet. Es wird ein Verständnis darüber vermittelt, wie sich Arbeitseinstellungen am Beginn der Transformation von einer Plan- zur Marktwirtschaft darstellen. Weiterhin werden die Veränderungen in den Einstellungen zur Arbeit aufgezeigt, die sich aufgrund des schwierigen Transformationsprozesses ergeben Eine praktische Konsequenz die sich aus den Untersuchungen ergibt ist, daß organisationaler Wandel nur erfolgreich ist, wenn er geplant und unter Berücksichtigung der Werte und Einstellungen der Mitarbeiter durchgeführt wird. Aus dieser Sicht ist die Implementation neuer HRM-Ansätze für einen erfolgreichen Wandel notwendig.
Keywords: 650